The management of service delivery : a case of Limpopo Department of Public Works - Holford, Michael G. (My University, 2015)
This study undertook to look into the management of service delivery by the Limpopo Department of Public Works. Over the past four years the researcher, through his interaction and work with departmental officials, identified various weaknesses with management. The study examines various literature relating to management and service delivery issues. A comprehensive review was made by the researcher of the available departmental documentation. The study method used was qualitative. A semi-structured questionnaire was developed and provided to management. This study found that indeed there are issues with management in the Limpopo Department of Public Works. Key findings were that the maturity and experience of management is critical to the functionality of an institution and that institutions need to embrace change, particularly within a technical environment.
Thesis (MPA.) -- University of Limpopo, 2015
Keywords: Service delivery; 352.140968; Public administration -- South Africa -- Limpopo; Local government -- South Africa -- Limpopo; Municipal services -- South Africa -- Limpopo